Nadine dreams of home - Ashley, Bernard (Edinburgh: Barrington Stoke, 2014)
"Nadine is afraid of London, and of her memories, and especially for her father, who didn't get out of Goma with the family. But then a kind teacher shows Nadine a photo of home, and Nadine learns to dream again"--Publisher's website
Keywords: Children's stories